Role of Ethylene in the Regulation of Plant Developmental Processes - Sheen Khan; Ameena Fatima Alvi; Nafees A. Khan (Stresses, 2024)
Ethylene, a gaseous phytohormone, is emerging as a central player in the intricate web of plant developmental processes from germination to senescence under optimal and stressed conditions. The presence of ethylene has been noted in different plant parts, including the stems, leaves, flowers, roots, seeds, and fruits. This review aims to provide a comprehensive overview of the regulatory impact of ethylene on pivotal plant developmental processes, such as cell division and elongation, senescence, abscission, fruit and flower development, root hair formation, chloroplast maturation, and photosynthesis. The review also encompasses ethylene biosynthesis and signaling: a snapshot of the regulatory mechanisms governing ethylene production. Understanding of the impact of ethylene’s regulatory functions on plant developmental processes has significant implications for agriculture, biotechnology, and our fundamental comprehension of plant biology. This review underscores the potential of ethylene to revolutionize plant development and crop management.